2011
DOI: 10.1261/rna.026658.111
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of RNA/RNA kissing complex: with application to HIV dimerization initiation signal

Abstract: We develop a statistical mechanical model to predict the structure and folding stability of the RNA/RNA kissing-loop complex. One of the key ingredients of the theory is the conformational entropy for the RNA/RNA kissing complex. We employ the recently developed virtual bond-based RNA folding model (Vfold model) to evaluate the entropy parameters for the different types of kissing loops. A benchmark test against experiments suggests that the entropy calculation is reliable. As an application of the model, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 99 publications
0
51
0
Order By: Relevance
“…In addition, the stable structure of the SL1/SL1 complex is a linear dimer, which is different from the kissing complex determined by previous NMR measurement for the truncated short SL1 sequence (Laughrea and Jette 1994;Muriaux et al 1996;Ennifar et al 2001;Paillart et al 2004;Ulyanov et al 2006). Our previous theoretical study (Cao and Chen 2011) on the truncated SL1 sequence also showed that the linear dimer and the kissing complex coexist at room temperature. However, the previous model cannot be used to predict the complex structure of the whole SL1 domain.…”
Section: Sl1/sl1 Complex In Hiv Virusmentioning
confidence: 82%
See 4 more Smart Citations
“…In addition, the stable structure of the SL1/SL1 complex is a linear dimer, which is different from the kissing complex determined by previous NMR measurement for the truncated short SL1 sequence (Laughrea and Jette 1994;Muriaux et al 1996;Ennifar et al 2001;Paillart et al 2004;Ulyanov et al 2006). Our previous theoretical study (Cao and Chen 2011) on the truncated SL1 sequence also showed that the linear dimer and the kissing complex coexist at room temperature. However, the previous model cannot be used to predict the complex structure of the whole SL1 domain.…”
Section: Sl1/sl1 Complex In Hiv Virusmentioning
confidence: 82%
“…We note that hairpin loop kissing complexes often favor the formation of coaxial stacking interactions. The entropy parameters for the hairpin kissing complexes listed in Table 1 of the article by Cao and Chen (2011) are for hairpin kissing systems with three helices coaxially stacked.…”
Section: Entropy Of Kissing Loopsmentioning
confidence: 99%
See 3 more Smart Citations